Classification of Sufi Groups in Malay Jawi Literature - Mohamad Nasrin Nasir, (Human Sustainability Procedia, 2018)
In a recent paper Professor Hamid Algar(Journal of Islamic Studies, Volume 29, Issue 1, 1 January 2018) had discussed the classification of troublesome sufi groupings into antinomians and fraudsters based upon Sufi sources themselves. It is seen there that there is a reference as to how mainstream Sufi had exposed these frauds so as to enable true Sufi adherents to avoid following their ideas. The Sufi sources referred to by Prof. Algar was immense and displayed how both the Sunni and Shia Muslims had exposed the lies and antinomian tendencies brought by them. This paper would attempt to do something similar but with special emphasis on the Malay Sufis and their writings. It is indeed a misguided attempt to believe that the Malay Sufis were independent from their counterparts in the west. For the Malays or the Jawi as they are known in the west or the Hijjaz were a significant group of Muslims domiciled in the holy cities of Mekkah and Madina. This paper would investigate the various groupings or fraud ideologies within the Sufis themselves as seen by the Malays in their own words. As the many groupings that were mentioned by Prof. Algar are domiciled in the west, it would be interesting to see whether such ideas as propagated by them had reached the Far East. The period under investigation would be dependent upon the first text that can be seen to have such discussion within them which is roughly in the 16th century up until the late 19th or early 20th century. It will be seen that authors of the Sufi texts were aware of those misguided from within them and understood the environment of Nusantara then. Their many writings were instructive as much as they were prescriptive.